Collaborative action research: building authentic literate practices into a foreign language program - Austin, Theresa; Blum, Mark (Colombian Applied Linguistics Journal, 2009)
Two university professors collaborate to carry out an action research project on literacy in a world language program. This article reports on their negotiations to define literacy, how they adapt the use of texts to the cultural backgrounds and interests of their learners and integrate native speakers in a community that builds various understanding of texts through discussion. Our collaborative process provides one example of how action research can systematically inform teaching and learning to build authentic literacy practices in a second or foreign language program.